(untitled) (Journal of Scientific Research, 2015)
Structural properties, impedance, dielectric and electric modulus spectra have been used to investigate the sintering temperature (Ts) effect on the single phase cubic spinel Ni0.6Zn0.4Fe2O4 (NZFO) ceramics synthesized by standard ceramic technique. Enhancement of dielectric constants is observed with increasing Ts. The collective contribution of n-type and p-type carriers yields a clear peak in notable unusual dielectric behavior is successfully explained by the Rezlescu model. The non-Debye type long range dielectric relaxation phenomena is explained by electric modulus formalism. Fast response of the grain boundaries of the sample sintered at lower Ts sample leading to small dielectric spin relaxation time, t (several nanoseconds) have been determined using electric modulus spectra for the samples sintered at different Ts. Two clear semicircles in impedance Cole-Cole plot have also been successfully explained by employing two parallel RC equivalent circuits in series configuration taking into account no electrode contribution. Such a long relaxation time in NZFO ceramics could suitably be used in nanoscale spintronic devices.